A Stochastic Frontier Production Function to Measure the Technical Efficiency of the Farmer of Apple (Malus Pumila) Production and Productivity - Rishabh Mohan; Chetan Kumar Saini; R.B. Singh; Neelash Patel (Journal of the Indian Society of Agricultural Statistics, 2025)
This paper estimates the Technical Efficiency (T.E.) of an apple-producing farmer in Jubbal and Kotkhai tahsil of Shimla district, using a stochastic Cobb-Douglas (CD) production frontier function. A stochastic frontier production function can be used for panel data of firms. The non-negative technical inefficiency effects are assumed to function firm-specific variables and vary over time. They are believed to be independently distributed as truncations of normal distributions with constant variance. The result shows the mean technical efficiency of Jubbal and Kotkhai tahsil Farmer is 66% and 70%. The mean technical efficiency is high for Kotkhai Farmer compared to Jubbal Farmer. Therefore, it is concluded that Kotkhai’s farmers are more technically efficient than Jubbal with the same input. This suggests that Jubbal Farmer can potentially increase their productivity through more efficient use of information.